2016
DOI: 10.1053/j.pcsu.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The Relentless Effects of the Fontan Paradox

Abstract: The Fontan operation is the anticipated palliative strategy for children born with single-ventricle type of congenital heart disease. As a result of important circulatory limitations, a series of end-organ complications are now increasingly recognized. Elevated central venous pressure and impaired cardiac output are the hallmarks of cavo-pulmonary flow, which result in a cascade of pathophysiological consequences. The Fontan circulation likely impacts all organ systems in an indolent and relentless manner, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
139
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(147 citation statements)
references
References 30 publications
(25 reference statements)
2
139
0
3
Order By: Relevance
“…One of the biggest barriers for successful transplants in the Fontan population is the underlying and poorly understood impact of subclinical liver failure. Fontan‐associated liver disease is highly prevalent, as these patients are exposed to systemic venous hypertension, hepatic congestion, and low cardiac output leading to various stages of liver disease ranging from clinically silent cirrhosis to hepatocellular carcinoma . A recent study found that adults with Fontan palliation universally have biopsy‐proven hepatic fibrosis despite normal synthetic function .…”
Section: Discussionmentioning
confidence: 99%
“…One of the biggest barriers for successful transplants in the Fontan population is the underlying and poorly understood impact of subclinical liver failure. Fontan‐associated liver disease is highly prevalent, as these patients are exposed to systemic venous hypertension, hepatic congestion, and low cardiac output leading to various stages of liver disease ranging from clinically silent cirrhosis to hepatocellular carcinoma . A recent study found that adults with Fontan palliation universally have biopsy‐proven hepatic fibrosis despite normal synthetic function .…”
Section: Discussionmentioning
confidence: 99%
“…Within years of Fontan completion, almost all patients are noted to develop hepatic fibrosis with some evolving to cirrhosis [91]. Some rare cases of hepatocarcinomas have also been described [49,92].…”
Section: Liver and Renal Failurementioning
confidence: 99%
“…[10] Ongoing physiological and psychosocial issues place a considerable burden on patients and their families with a significant reduction in quality of life. [11] Whilst there are expectations of improving outcomes,[12] the Fontan circulation remains a life-limiting condition with limited treatment options; it is the highest risk diagnosis for heart transplantation yet is the least amenable to mechanical circulatory support.…”
Section: Introductionmentioning
confidence: 99%